Unusual Fermi‐Level Pinning and Ohmic Contact at Monolayer Bi2O2Se–Metal Interface. Issue 5 (26th February 2019) - Liu, Shiqi; Xu, Lianqiang; Pan, Yuanyuan; Yang, Jie; Li, Jingzhen; Zhang, Xiuying; Xu, Lin; Pang, Hua; Yan, Jiahuan; Shi, Bowen; Sun, Xiaotian; Zhang, Han; et al.
Abstract: Very recently, high‐mobility and air‐stable 2D semiconductor Bi2 O2 Se has been discovered and believed to be a promising channel candidate for the next‐generation field‐effect transistor (FET). High‐performance few‐layer Bi2 O2 Se FETs have been realized due to the existence of ohmic contact between few‐layer Bi2 O2 Se and the metal electrodes. However, monolayer (ML) Bi2 O2 Se FET exhibits poor device performance owing to lack of good contact between ML Bi2 O2 Se and the metal electrode. This work simulates the ML Bi2 O2 Se Schottky barrier field‐effect transistors with a sequence of common electrodes (Au, Pd, Pt, Ag, Sc, and Ti) for the first time by using ab initio quantum transport simulations. For Ag, Au, and Pd electrodes, a lateral n ‐type Schottky contact is formed with similar Schottky barrier heights of 0.43–0.52 eV due to a strong usual Fermi‐level pinning (FLP) to the band gap of ML Bi2 O2 Se. Remarkably, Pt, Sc, and Ti electrodes lead to a desirable lateral n ‐type ohmic contact because of an unusual FLP above the ML Bi2 O2 Se conduction band as a result of electrode work function modification at the interface. Therefore, high performance is anticipated for ML Bi2 O2 Se devices with these low‐resistance ohmic contacts. Abstract : This work simulates the ML Bi2 O2 Se Schottky barrier field‐effect transistor with a sequence of common electrodes . Ag, Au, and Pd electrodes form lateral n ‐type Schottky contacts. Remarkably, a desirable lateral n ‐type ohmic contact is generated with Pt, Sc, and Ti electrodes. Therefore, high performance is anticipated for ML Bi2 O2 Se devices with these low‐resistance ohmic contacts.